European Union, populism and religious minorities: complex entanglements. Issue 4 (8th August 2021) - Giorgi, Alberta
ABSTRACT: Research shows that, overall, the EU has a positive impact on the respect of religious diversity in the multi-level European system and that religious minorities have a positive attitude toward the EU. This positive, albeit limited, impact may be endangered by the rise of the right-wing populist discourse which, as many scholars have shown, targets minorities, and religious minorities in particular. The purpose of this article is to explore the role that populism plays in the EU-orientation of religious groups. Drawing on the case study of Italy, the analysis shows that the majority of religious groups take a stance against populism and promote inter-religious solidarity, and that while most religious groups perceive that the EU has a positive role to play, their action is specially oriented at the local level.